ANALISIS STRATEGI PENGEMBANGAN BISNIS MENGGUNAKAN METODE SWOT DAN QUANTITATIVE STRATEGIC PLANNING MATRIX PADA STARTUP SAYURLELI - Indah Laili Suqya Rahmad; Yesica Novrita Devi; Danis Maulana (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
Startup Sayurleli is a startup that offers a H+1 fresh vegetable ordering service. The development of Sayurleli Startup seems slow. This happens because information technology is lagging behind in this business. This is proven by Sayurleli's unstable income during operation from 2021 to 2023. This research aims to determine alternative business development strategies for Sayurleli Startup using the data collection technique method using the QSPM (Quantitative Strategic Planning Matrix) method with the IFE matrix, EFE matrix, IE matrix and SWOT matrix as research calculation tools. The results obtained were that there were 11 internal factors consisting of 7 strength factors and 4 weakness factors and there were 10 external factors consisting of 6 opportunity factors and 4 threat factors and based on the SWOT matrix, there were 17 strategies that vegetable can apply. The results of the research analysis show that Stratup is in cell II position, which means growth and development and Intensive Strategy there are 3 alternative strategies, namely market penetration with a TAS score of 6.29, market development with a TAS score of 6.42 and product development of 6.518. The final results of the research show that the priority strategy that can develop business is product development.